Factors associated with intentional and unintentional non‐adherence to adjuvant endocrine therapy following breast cancer. (30th November 2016) - Brett, J.; Fenlon, D.; Boulton, M.; Hulbert‐Williams, N.J.; Walter, F.M.; Donnelly, P.; Lavery, B.; Morgan, A.; Morris, C.; Watson, E.
Abstract : Adherence to adjuvant endocrine therapy (AET) following breast cancer is known to be suboptimal despite its known efficacy in reducing recurrence and mortality. This study aims to investigate factors associated with non‐adherence and inform the development of interventions to support women and promote adherence. A questionnaire survey to measure level of adherence, side effects experienced, beliefs about medicine, support received and socio‐demographic details was sent to 292 women 2–4 years post breast cancer diagnosis. Differences between non‐adherers and adherers to AET were explored, and factors associated with intentional and unintentional non‐adherence are reported. Approximately one quarter of respondents, 46 (22%), were non‐adherers, comprising 29 (14%) intentional non‐adherers and 17 (8%) unintentional non‐adherers. Factors significantly associated with intentional non‐adherence were the presence of side effects ( p < .03), greater concerns about AET ( p < .001) and a lower perceived necessity to take AET ( p < .001). Half of the sample (105/211) reported that side effects had a moderate or high impact on their quality of life. Factors associated with unintentional non‐adherence were younger age (<65) ( p < .001), post‐secondary education ( p = .046) and paid employment ( p = .031). There are distinct differences between intentional non‐adherence and unintentional non‐adherence. Differentiation between the two types of non‐adherence may help tailor support and advice interventions.